Keterkaitan Mekanisme Pengelolaan Kas dan Belanja Pemerintah Pusat dan Daerah: Upaya Mengatasi Idle cash dalam Keuangan Negara: The Linkage of Cash and Expenditure Management Mechanisms between Central and Regional Governments: Efforts to Overcome Idle cash in Public Finance - Achmat Subekan; Ali Said; Haris Premadi; Sri Mahendra Satria Wirawan; Azwar, Azwar (Litera Academica Publishing, 2025)
This study aims to examine the linkage between cash and expenditure management mechanisms in the central and regional governments, particularly in relation to efforts to address idle cash in public finance. The research employs a qualitative approach, based on the consideration that the complexity of fiscal issues cannot be sufficiently explained through quantitative methods alone, but requires an in-depth exploration of processes, policies, and inter-agency synergies. The findings indicate that the central government has implemented cash and expenditure management in accordance with the mandates of the State Finance Law and the State Treasury Law. The measures undertaken include the implementation of a treasury single account, improvements to revenue and expenditure systems, cash planning, prudent fund placement, as well as the development of innovations to optimize cash management. In addition, a treasury dealing room has been established to monitor, analyze, and provide recommendations regarding cash inflows and outflows from the State General Cash Account (RKUN), thereby ensuring liquidity is maintained and idle cash minimized. This study contributes to the literature on public cash management by emphasizing the importance of integrating central and regional mechanisms. Practically, the findings provide insights for policymakers on the need for cross-institutional synergy and the utilization of coordinative forums to safeguard fiscal stability. Thus, cash management strategies can function not only as administrative instruments but also as strategic tools in supporting national development.